Aerobic granulation utilizing fermented municipal wastewater under low pH and alkalinity conditions in a sequencing batch reactor - Leong, Jason (Environmental technology, 2016)
The aim of this study was to achieve aerobic granulation utilizing fermented municipal wastewater under low pH, and alkalinity conditions. Stable granulation was achieved after a 166-day start-up period. Due to low influent strength, supplemental carbon addition, in the form of sucrose, was added to the feed storage tank on the 82nd day of start-up to facilitate granulation. This increased the system's organic loading rate from 1.43 ± 0.14 to 2.53 ± 0.18 kg COD/m(3)/d, and reduced the influent pH due to fermentation of the added sucrose. Although granulation was successful, the nutrient removal was limited. Removal rates at an influent pH of 6.23 ± 0.06 were 54.4% ± 8.3% for phosphorus, 21.9% ± 4.1% for ammonium, and 84.0% ± 3.0% for total chemical oxygen demand (COD). During the second phase of experimentation, increased amounts of sucrose were added to the feed, which resulted in increased volatile fatty acid concentrations and pH reduction to 5.62 ± 0.12 due to fermentation. Under further reduced pH conditions, phosphorus, ammonium, and total COD removal were found to be 58.9% ± 4.7%, 37.9% ± 4.7%, and 87.1% ± 0.9%, respectively. Settling volume indexes, SVI10 and SVI30, were found to be 148.8 ± 28.9 mL/g, for the influent pH of 6.23 ± 0.06, and 157.5 ± 40.6 mL/g, for the influent pH of 5.62 ± 0.12. This high SVI is indicative of the formation of lower-density granules in comparison to high-ash-content granules. The absence of denitrification-induced chemical phosphorus precipitation within the granule was likely a contributing factor to the low granule density observed in the system